East of Eden Premire. - 20th Century Fox:::Creator::::::::::::
Formal party at the premiere of East of Eden; clockwise, starting on the left, at the top of the table, Elaine Steinbeck, John Steinbeck, unknown, Elia Kazan, Molly Kazan, Jack Warner, unknown, unknown, Dorothy Massey, Raymond Massey.